Fish kept in an ice-filled container - Mumbai Archive Project Team (Jio Institute, 2024)
Fish is preserved in ice to keep it fresh during storage and shipping. Fish kept in an ice-filled container helps maintain freshness and quality by delaying spoiling and bacterial growth.